The remembrance of the Street fair in José Gonçalves District in Vitória da Conquista – BA - Sampaio, Andrecksa Viana Oliveira; Menezes, Sônia de Souza Mendonça (Geografares, 2020)
This article presents the memory of the street market in José Gonçalves, Vitória da Conquista district, through the narratives of the residents. The street fair represented a time of prosperous trade, with circulation of people and goods, but some social and economic factors contributed to the end of it: the drought that hit the district in the 1980s, the coffee growing in the municipality of Vitória da Conquista, the coffee harvest that brought the illusion of a more profitable work, among others. Currently, this street market exists only in the collective memory of the population that lived and is driven to narrate these remembrances